Measuring the impact of managing incontinence on people with dementia and informal caregivers: Cognitive debriefing interviews of ‘ICIQ-Cog’ (English translation) - Miriam Avery; Nikki Cotterill; Mandy Fader; Margaret Macaulay; Ruth Kirschner-Hermanns; Cathy Murphy (Continence)
Aim:: The ICIQ-Cog questionnaire was developed in German to measure the impact of incontinence and/or toilet use problems on people living with dementia and their paid carers and unpaid caregivers; it has been translated into English. This study aimed to (1) examine the linguistic validity of the ICIQ-Cog English translation and (2) determine whether it addresses what is important to unpaid caregivers. Methods:: Cognitive debriefing interviews were conducted with 13 unpaid caregivers of people with dementia and problems with incontinence or toilet use recruited via Joint Dementia Research. Interviews were conducted across 3 rounds and transcribed then thematically analysed based on the questionnaire framework. Results:: All participants were unpaid caregivers; they highlighted the need for the questionnaire. Changes were made to the title and response options were added to 10 of 12 questions; wording changes were made to 5 questions. One of the questions was deemed difficult to answer as an unpaid caregiver due to the need for more general caring experience; another used phraseology potentially more understandable by professional carers. Several participants emphasised missing questions (such as cost of buying continence aids and extra washing). The interviews were halted because the questionnaire did not fully meet unpaid caregivers needs. Conclusion:: This linguistic validation of the ICIQ-Cog questionnaire identified that it is not appropriate for use among unpaid caregivers. A questionnaire to assess impact of managing incontinence designed purposefully for unpaid caregivers of a person with dementia is needed. Further work is required to finalise the English translation for paid carers.